Hubungan antara Manajemen Waktu dan Kesehatan Mental pada Mahasiswa - Elsa Safitri; Niar Setya Iassha Putri; Lesi Sucianti Sihaloho; Sri Mulyeni (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Time management and mental health are two closely related aspects of students’ academic life. Academic demands, numerous assignments, and pressure to achieve good academic performance often affect students’ psychological conditions and their ability to manage time effectively. This study aims to determine the relationship between mental health and time management skills among active university students. The research used a quantitative survey method by distributing online questionnaires (Google Forms) to 41 respondents from various study programs. Mental health served as the independent variable, while time management was the dependent variable, measured using a five-point response scale. Data were analyzed using SPSS through validity, reliability, and ANOVA tests. The results showed that all instruments had good validity and reliability, indicated by high Cronbach’s Alpha values. Inferential analysis revealed a significance level below the statistical threshold, confirming a significant influence of mental health on time management with a contribution of 60.3%. These findings indicate that students with stable psychological conditions are more capable of organizing priorities and schedules effectively. Therefore, institutional support for students’ mental well-being is essential to support academic success.